The Psychoeducation Model: Definition, Contemporary Roots and Content - Authier, Jerry (Canadian Journal of Counselling and Psychotherapy, 2012)
Psychoeducation is a therapeutic approach under which the psychological practitioner's functioning is viewed not in terms of abnormality (or illness) diagnoses prescription — therapy –> cure; but rather in terms of client dissatisfaction (or ambition) –> goal-setting — skill-teaching –> satisfaction or goal achievement. The contemporary roots of psychoeducation are traced from an early era serving to set the stage for psychotherapy as an educational process, to the behavior modification era, to the community mental health era. Content ofpsychoeducation is discussed in terms of general skills (i.e., communication skills, interpersonal skills, relationship skills, etc.) and specific skills (i.e., coping with frustration, sexual satisfaction, handling aggressive impulses, etc.). It is concluded psychoeducation content is limited only by the imagination of the persons seekinghelp and by the ability of the psychological practitioner to be innovative and creative enough to design a systematic program for teaching clients the psychological self-help that will make their lives more fulfilling.